Doe applied to study the effect of process parameters on silicon spacing in lost foam Al-Si-Cu alloy casting - Shayganpour, Amir Reza (2012)
Lost foam casting as a relatively new manufacturing process is extensively employed to produce sound complicated castings. In this study, an experimental investigation on lost foam casting of an Al-Si-Cu aluminium cast alloy was conducted. The research was aimed in evaluating the effect of different pouring temperatures, slurry viscosities, vibration durations and sand grain sizes on eutectic silicon spacing of thin-wall castings. A stepped-pattern was used in the study and the focus of the investigations was at the thinnest 3 mm section. A full two-level factorial design experimental technique was used to plan the experiments and afterwards identify the significant factors affecting casting silicon spacing. The results showed that pouring temperature and its interaction with vibration time have pronounced effect on eutectic silicon phase size. Increasing pouring temperature coarsened the eutectic silicon spacing while the higher vibration time diminished coarsening effect. Moreover, no significant effects on silicon spacing were found with variation of sand size and slurry viscosity.